TIMBULAN SAMPAH KAWASAN KANTOR BPPT - Rosita Shochib (BPPT)
Solid Waste genartion is amount of wastes generated by a given source or category of. Sources per day in weight or volume. Data of waste generation is necessary in design of solid waste management system. For that purpose, a research about waste generation will be performed. The analysis is focused to office solid waste, base on SNI 19-3964-1994 for 8 days. Based on waste collection, the sourses of office solid waste are working place, Canteen, and yard. The research’s result shows that everage of office solid waste generation in BPPT is 0.15 kg/employee/day or 0.222 kg/sq meter/perday in weightKeywords : office waste generation, waste, waste collection, sources of office waste, unity of solid waste